A Content Analysis of Popular YouTube Channels Regarding Children’s Food and Nutrition Literacy - Şakar, Gizem Nur; Mumcuoğlu, Ayşenur; Demirci, Güneş Ezgi; Erden, Feyza Tantekin (Journal of Childhood Studies)

(untitled) (Canadian Association for Young Children, 2026)
This study evaluates the content of the most popular YouTube videos worldwide in terms of the presence of messages that support or hinder children’s food and nutrition literacy, using Azam Doustmohammadian and colleagues’ conceptual framework of food and nutrition literacy in children. Forty-four food-related videos were selected from the three most popular child-themed YouTube channels. The results revealed that the cognitive aspects of the framework were slightly supported in the selected videos; however, negative messages were prevalent. Although there was no positive content to support children’s food and nutrition literacy regarding interactive, emotional, and discussion skills, it was found that only contradictory messages were given in the emotional skills dimension. Another significant aspect of the findings, as discussed through the lens of childhood studies, is that certain types of eating behaviours were presented as more favourable than others, and many subtle moral messages were detected regarding normative assumptions about bodies, health, and food practices.